Computer-mediated text-based and audio-based corrective feedback, perceptual style and L2 development. (June 2019) - Rassaei, Ehsan
Abstract: The present study investigates the effects of computer-mediated text-based and audio-based corrective feedback (CF) along with the moderating effects of the participants' preferred perceptual style on the development of the English article system by Iranian EFL learners. The study includes 89 intermediate level learners who were assigned to computer-mediated text-based, audio-based and control conditions. The participants were also identified in terms of whether their preferred perceptual style was read/write or auditory based on their answers to a perceptual style inventory. During treatment sessions, the participants of the experimental groups performed several written production tasks and depending on their treatment condition received either asynchronous text-based or audio-based CF for their errors. Two testing instruments, an oral production task and a writing task, were used to measure learners' improvement as a result of the treatment tasks. Findings indicate that both text-based and audio-based CF are effective for L2 development while audio-based CF is more effective than text-based CF. Furthermore, the results provide evidence that matching CF modality with learners' perceptual style further promotes the effectiveness of computer-mediated CF.